Comparative effectiveness of rhythmic grip training of various intensities on cognitive function in young adults: a fNIRS study - Zhu, Huming; Han, Yanbai; Wang, Mengzhao; Cheng, Zhuoyue; Du, Mingrui; Jiang, Huilin; Wang, Hongli (Frontiers in Neuroscience, 2025)
IntroductionResistance training has a significant influence on cognitive function. Rhythmic handgrip (RHG) exercise, a practical form of small-muscle group training, may improve cognitive performance. However, the effects of resistance training at various intensities on prefrontal cortex (PFC) activation and cognitive outcomes remain unclear.MethodsThis study recruited 24 healthy male participants (mean age: 22.39 ± 1.31 years). Participants completed experiments at three intensity levels [30%, 50%, and 70% Maximum Voluntary Contraction (MVC)] in a randomized order, with one-week intervals between sessions. During dynamic handgrip resistance training, participants performed rhythmic fist contractions at the target intensity, maintaining a frequency of 1 Hz for 30 s, followed by 30 s of rest. Each training set consisted of four contraction-rest cycles, and participants completed three sets in total, separated by 3-min rest periods. Cognitive task testing including the Stroop task, 2-Back task, and More-Odd Shifting task, was administered before and after each intervention. Cognitive performance was evaluated using reaction time and accuracy measures. Simultaneously, functional near-infrared spectroscopy was employed to measure changes in oxygenated hemoglobin (HbO2) levels in the prefrontal cortex during task execution.ResultsThe moderate-intensity (50% MVC) rhythmic handgrip task produced the greatest improvements in cognitive performance. Behaviorally, participants showed faster reaction times and higher accuracy than in low- (30% MVC) or high-intensity (70% MVC) conditions. Functional near-infrared spectroscopy results showed that moderate-intensity rhythmic handgrip enhanced the efficiency of prefrontal modulation, particularly in the dorsolateral prefrontal cortex and inferior frontal gyrus. The 50% MVC condition reduced oxygenated hemoglobin levels, indicating optimized neural efficiency and more effective cortical resource allocation during task performance.ConclusionModerate-intensity (50% MVC) RHG training significantly enhances executive function, working memory, and cognitive flexibility, while demonstrating more efficient neural activity. As a practical form of small-muscle-group training, moderate-intensity RHG resistance offers a promising early-intervention strategy for delaying cognitive decline and reducing dementia risk.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2400083689.